Brill's companion to Thucydides - Rengakos, Antonios; Tsakmakis, Antonis (Leiden ; Boston : Brill, 2006)
This volume on Thucydides, the most important historian of the ancient world, comprises articles by thirty leading international scholars. The contributions cover a wide range of issues, including Thucydides' life, intellectual milieu and predecessors, Thucydides and the act of writing, his rhetoric, historical method and narrative techniques, narrative unity in the History, the speeches, Thucydides' reliability as a historian, and his legacy through the centuries. Other topics dealt with include warfare, religion, individuals, democracy and oligarchy, the invention of political science, Thucydides and Athens, Sparta, Macedonia/Thrace, Sicily/South Italy, Persia, and the Argives. The volume aims to provide a survey of current trends in Thucydidean studies which will be of interest to all students of ancient history.
Macedonia and Thrace in Thucydides / Michael Zahrnt -- Thucydides and the Argives / Simon Hornblower -- Sicily and Southern Italy in Thucydides / Michael Zahrnt -- ". . . keeping the two sides equal" : Thucydides, the Persians and the Peloponnesian War / Josef Wiesenhofer -- Peloponnesian War : Sources Other Than Thucydides / Martin Hose -- Thucydides Continued / Roberto Nicolai -- Thucydides in Rome and Late Antiquity / Luciano Canfora -- Byzantine Adaptations of Thucydides / Diether Roderich Reinsch -- Thucydides' Rennaissance Readers / Marianne Pade -- Thucydidean Modernities: History between Science and Art / Francisco Murari Pires.
Includes bibliographical references (pages 839-882) and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Thucydides; Thucydide; History of the Peloponnesian War (Thucydides); Thucydides; Thucydides; Greece -- History -- Peloponnesian War, 431-404 B.C. -- Historiography; Grèce -- Histoire -- 431-404 av. J.-C. (Guerre du Péloponnèse) -- Historiographie; HISTORY -- Ancient; Historiography; Greece; Historiae (Thucydides); Historiografia -- Grécia antiga; Historians -- Greece; Greece -- Historiography; Greece -- History -- Peloponnesian War, 431-404 B.C. -- Historiography; Peloponnesiska kriget 431-404 f. Kr; 431-404 B.C; History; Handboeken (vorm)